Perioperative outcomes and survival of octogenarians undergoing curative resection for esophagogastric adenocarcinoma. Issue 6 (23rd February 2020) - Chen, Eric; Senders, Zachary J; Hardacre, Jeffrey; Kim, Julian; Ammori, John
Abstract: Background and Objectives: Current data are conflicting as to whether the outcomes of octogenarians undergoing resection for esophagogastric adenocarcinoma are comparable to younger patients. This study aims to compare perioperative outcomes and survival of patients ≥80 years old with younger patients undergoing curative resection for esophagogastric adenocarcinoma. Methods: Retrospective data were collected on 190 patients who underwent resection with curative intent for adenocarcinomas found in the stomach and esophagogastric junction from 2004 to 2015 at a single institution. Results: Of the 190 patients, 34 (18%) were ≥80 years old. Octogenarians were more likely to have chronic kidney disease (CKD) and were less likely to have received neoadjuvant chemotherapy. Pathologic features were similar between groups. Octogenarians' tumors were more likely to be located in the gastric body as compared to the esophagogastric junction in younger patients. Although the length of stay was comparable, octogenarians were significantly less likely to be discharged home ( P  < .01). Both groups had a single death during the index admission. Incidence and severity of 90 days postoperative complications were not significantly different between groups. There was no difference in 30‐day, 90‐day, 1‐year, or median survival. Conclusions: Perioperative outcomes and survival of octogenarians undergoing curative resection for esophagogastric cancer are comparable to younger patients at our institution.